Epigenetically modulated FOXM1 suppresses dendritic cell maturation in pancreatic cancer and colon cancer. Issue 4 (15th February 2019) - Zhou, Zhongshi; Chen, Hongdan; Xie, Rui; Wang, Hongjie; Li, Senlin; Xu, Qianqian; Xu, Na; Cheng, Qi; Qian, Ying; Huang, Rongrong; Shao, Zekun; Xiang, Ming
Abstract : Forkhead box transcription factor M1 (FOXM1) is a proliferation‐associated transcription factor involved in tumorigenesis through transcriptional regulation of its target genes in various cells, including dendritic cells (DCs). Although previous work has shown that FOXM1 enhances DC maturation in response to house dust mite allergens, it is not known whether FOXM1 affects DC maturation in the context of tumor‐specific immunity. In this study, we examined the central role of FOXM1 in regulating bone marrow‐derived dendritic cell (BMDC) maturation phenotypes and function in pancreatic cancer and colon cancer. FOXM1 retarded maturation phenotypes of BMDCs, inhibited promotion of T‐cell proliferation, and decreased interleukin‐12 (IL‐12) p70 in tumor‐bearing mice (TBM). Notably, FOXM1 expression was epigenetically regulated by dimethylation on H3 lysine 79 (H3K79me2), a modification present in both tumor cells and BMDCs. Increased H3K79me2 enrichment was observed at the FOXM1 promoter in both BMDCs from TBM, and in BMDCs from wild‐type mice cultured with tumor‐conditioned medium that mimics the tumor microenvironment (TME). Furthermore, inhibition of the H3K79 methyltransferase DOT1L not only decreased enrichment of H3K79me2, but also downregulated expression of FOXM1 and partially reversed its immunosuppressive effects on BMDCs. Furthermore, we found that FOXM1 upregulated transcription of Wnt family number 5A (Wnt5a) in BMDCs in vitro ; we also observed that exogenous Wnt5a expression abrogated BMDC maturation phenotypes by inhibiting FOXM1 and H3K79me2 modification. Therefore, our results reveal that upregulation of FOXM1 by H3K79me2 in pancreatic cancer and colon cancer significantly inhibits maturation phenotypes and function of BMDCs through the Wnt5a signaling pathway, and thus provide novel insights into FOXM1‐based antitumor immunotherapy. Abstract : Here, we demonstrate that (a) the transcription of FOXM1 is upregulated by the H3K79me2 modification; (b) FOXM1 suppresses the maturation of BMDCs via direct activation of Wnt5a and weakens promotion of T cell proliferation; and (c) FOXM1 also enhances tumorigenesis by upregulating CCNA2 and CCNB1 in tumors. We conclude that targeting histone methylation of FOXM1 may be useful for anti‐tumor immunotherapy.